A new miocene–pliocene ichnotaxon for vermetid anchoring bioerosion structures - Verde, Mariano; Castillo, Carolina; Martín-González, Esther; Cruzado-Caballero, Penélope; Mayoral, Eduardo; Santos, Ana (Frontiers in Earth Science, 2022)
A revision of Renichnus arcuatus Mayoral, 1987, the vermetid attachment etching trace fossil (fixichnia), is presented here with an emended diagnosis. Renichnus arcuatus should be used only for nested reniform depressions arranged in linear series or solitary ones. A new ichnotaxon, Santichnus mayorali ichnogen. et ichnosp. nov. is described in order to name a bioerosion structure that previous authors included under R. arcuatus. The new trace fossil comes from the Miocene-Pliocene deposits from Fuerteventura and Lanzarote, Canary Islands, and is characterized as a shallow canal, semicircular in cross-section that occurs in the surface of hard substrates. Santichnus mayorali follows a logarithmic spiral path that may depart in its outer whorl in a somewhat straight shaft that becomes recurved back towards the spiral. From an actualistic point of view, this new ichnotaxon is interpreted as the anchorage bioerosion structure of vermetid gastropods. Given the close relationship between the two ichnotaxa (Renichnus and Santichnus) that share vermetid gastropods as their tracemakers, it is proposed that they be considered as a compound trace fossil when they occur interconnected.